IMPLEMENTASI KONSEP PENGEMBANGAN MUTU PADA PEMBELAJARAN DINIYAH - Sintiyani Sintiyani; Sunhaji Sunhaji (STAI Sufyan Tsauri Majenang, 2020)
The issue of Full Day School is considered a threat to the existence of diniyah education. In fact, religious learning in schools has not been able to meet the needs of students. Responding to the this issue, diniyah education institutions must be able to improve the quality of their learning. This paper describes the main concepts of diniyah learning and how to implement the concept of quality development in diniyah learning. The result show that diniyah learning is a process where learning interactions are illahiyah and basyariyah between students, educators and learning environment. The development of the quality of diniyah learning can be carried out with the concept of development of school learning which is implemented based on Islamic guidance and still adheres to the characteristics of diniyah education. Balanced collaboration between the application of the thought of educational figures with the unique concept of diniyah education will result in better quality learning.